Problem with pulse action for systems with Bessel?Kolmogorov operators - Konarovska, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We construct the fundamental matrix of solutions of the Cauchy problem and a problem with impulse action for systems with Bessel - Kolmogorov operators degenerate in all space variables. Estimates for the fundamental matrix are obtained, and its properties are established.